Newly identified T cell subsets in mechanistic studies of food immunotherapy - Sampath, Vanitha; Nadeau, Kari C. (The Journal of clinical investigation, 2019)
Allergen-specific immunotherapy has shown promise for the treatment of food allergy and is currently being evaluated in clinical trials. Although immunotherapy can induce desensitization, the mechanisms underlying this process are not completely understood. Recent advances in high-throughput technologies along with concomitant advances in data analytics have enabled monitoring of cells at the single-cell level and increased the research focus on upstream cellular factors involved in the efficacy of immunotherapy, particularly the role of T cells. As our appreciation of different T cell subsets and their plasticity increases, the initial simplistic view that restoring Th1/Th2 balance by decreasing Th2 or increasing Th1 responses can ameliorate food allergy is being enhanced by a more complex model involving other T cell subsets, particularly Tregs. In this Review, we focus on the current understanding of T cell functions in food allergy, tolerance, and immunotherapy.